Conceptualising and measuring 'employablity' - lessons from a National OLT Project. - Smith, C.; Ferns, Sonia; Russell, L. (2014)
The notion that employability should be an explicit outcome of higher education degrees is gaining traction in Australia, the U.K. and elsewhere. It is especially relevant to generalist and semi-professional degrees where the pathway to employment than it is for some professional degrees. To be able to promote employability as a worthwhile and sensible outcome of higher education, it is necessary to be able to determine what cluster of abilities should be taken to constitute employability. This paper reports on the results of a national project “Measuring the impact of WIL on student work-readiness”, and focuses on a confirmatory factor analysis of 6 dimensions of ability adopted by the study. It explores the provenance and utility of these measures for future employability research. The dimensions explored are: lifelong learning; professional practices and standards; integration of knowledge/theory and practice; informed decision making (applied information literacy); commencement readiness; and collaboration.